Anchor universities and communities: The power of community engagement - Johnson, B. J.; Hlatshwayo, M. (South African Journal of Higher Education, 2025)
Engaging with communities and the public is a powerful role that universities can play in anchoring themselves in society. In this paper, we argue that to fulfil this role effectively, universities must be conceptualised differently, moving beyond the notion of their three missions, with community engagement no longer treated as an afterthought. We propose the helix conception, a combination of Cooper’s (2017) “quadruple helix” and Carayannis, Barth and Campbell’s (2012) “quintuple helix”, as a theoretical and practical approach to restructuring how universities anchor society, especially during the challenging time of the “polycrisis”.